Innovative Ways to Develop Metacompetence in The Context of Digital Technologies - Jumanazarovich, Xurramov Anvar; Abdullayevich, Tashkarayev Ibrohim (Research Parks Publishers, 2025)
The article considers and analyzes the views of leading foreign scientists on the problem of meta-subjectivity within the framework of a competency-based approach to education. Regardless of the scope of implementation, the article is devoted to the problem of developing a competency-based approach to education in the context of expanding the types of competences when considering meta-competence beyond the subject as a methodological approach to search activities. The relevance of the formation of methods of metacognitive activity in the topic is determined by the new conditions of modern human life, which are characterized by high dynamics, lead to uncertainty, unpredictable situations and require continuous effective self-education. The categories of meta-objectivity are identified and the author's definitions of the concepts of meta-competence and meta-competence are proposed.